Relationship between Perceived Organizational Support and Organizational Citizenship Behaviour of Academic Staff in Malaysian Research Universities - Hassan, Roshafiza; Basri, Ramli; Asimiran, Soaib (International Journal of Psychosocial Rehabilitation, 2020)
This study examined the relationship between perceived organizational support and organizational citizenship behaviour of academic staff in Malaysian Research Universities. This study employed a quantitative descriptive survey whereby a total of 372 academic staff from five Research Universities were selected as samples for the study. A multistage random clustered sampling method was applied in sampling selection. An instrument consisting of 32 items were used to measure academic staff’ perceptions towards their level of organizational citizenship behaviour (24-items) and perceived organizational support (8-items) at the workplace. The data were collected and analyzed using descriptive statistical tools such as frequency, percentage, mean, and standard deviation while the research hypotheses were analyzed using inferential statistical tools such as Pearson correlation. The descriptive analysis showed that the level of organizational citizenship behaviour (mean = 5.91, SD = 0.56) was high while the level of perceived organizational support (mean = 4.80, SD = 1.10) was reported as moderate. The result of this study also found that there is a significant relationship between perceived organizational support and organizational citizenship behaviour (r = 0.346, p < 0.05). Even though it was concluded that the relationship was low, however, perceived organizational support was confirmed as contextual factors within academic staff in Malaysian Research Universities that would significantly contribute to their level of citizenship behaviour toward the organization they served for.